'Molecular photography': velocity-map imaging of chemical events. - Vallance, C (2004)
Every chemical reaction bears its own unique fingerprint, embodied in the kinetic energy, angular distribution and rotational and vibrational motion of the newly formed reaction products. These quantities reflect the forces acting during the chemical reaction, and their measurement often provides unparalleled insight into the basic physics governing chemical reactivity. One experimental technique that has truly captured the imagination of the reaction-dynamics community is velocity-map ion imaging, which provides a visual 'snapshot' of the complete product scattering distribution in a single measurement. Originally developed to study gas-phase photodissociation, the technique is now routinely being applied to bimolecular processes, particularly inelastic and reactive scattering. This article will review recent developments in the field, using examples from studies of a range of chemical processes.